Quantification of the functional expression of the Ca2+‐activated K+ channel KCa3.1 on microglia from adult human neocortical tissue. Issue 12 (29th July 2016) - Blomster, Linda V.; Strøbæk, Dorte; Hougaard, Charlotte; Klein, Jessica; Pinborg, Lars H.; Mikkelsen, Jens D.; Christophersen, Palle
Abstract : The KCa 3.1 channel ( KCNN4 ) is an important modulator of microglia responses in rodents, but no information exists on functional expression on microglia from human adults. We isolated and cultured microglia (max 1% astrocytes, no neurons or oligodendrocytes) from neocortex surgically removed from epilepsy patients and employed electrophysiological whole‐cell measurements and selective pharmacological tools to elucidate functional expression of KCa 3.1. The channel expression was demonstrated as a significant increase in the voltage‐independent current by NS309, a KCa 3.1/KCa 2 activator, followed by full inhibition upon co‐application with NS6180, a highly selective KCa 3.1 inhibitor. A major fraction (79%) of unstimulated human microglia expressed KCa 3.1, and the difference in current between full activation and inhibition (ΔKCa 3.1) was estimated at 292 ± 48 pA at −40 mV ( n  = 75), which equals at least 585 channels per cell. Serial KCa 3.1 activation/inhibition significantly hyperpolarized/depolarized the membrane potential. The isolated human microglia were potently activated by lipopolysaccharide (LPS) shown as a prominent increase in TNF‐α production. However, incubation with LPS neither changed the KCa 3.1 current nor the fraction of KCa 3.1 expressing cells. In contrast, the anti‐inflammatory cytokine IL‐4 slightly increased the KCa 3.1 current per cell, but as the membrane area also increased, there was no significant change in channel density. A large fraction of the microglia also expressed a voltage‐dependent current sensitive to the KCa 1.1 modulators NS1619 and Paxilline and an inward‐rectifying current with the characteristics of a Kir channel. The high functional expression of KCa 3.1 in microglia from epilepsy patients accentuates the need for further investigations of its role in neuropathological processes. GLIA 2016;64:2065–2078 Main Points: K + currents in primary human microglia are mainly due to Ca 2+ ‐activated K + channels. Electrophysiology and pharmacology revealed functional KCa 3.1 and KCa 1.1 in a majority of microglia. IL‐4 or LPS treatment did not change the KCa 3.1 current density.